Influence of the boreal summer intraseasonal oscillation on temperature and precipitation in South Korea - Yoo‐Rim Jung; Woo‐Seop Lee (Atmospheric Science Letters)
Abstract The boreal summer intraseasonal oscillation (BSISO) is a major mode of sub‐seasonal variability that regulates the summer climate in East Asia. This study investigates the four possible effects of two different time‐scale BSISOs on temperature and precipitation variations in South Korea. When active BSISO convection is positioned over the subtropical western Pacific, it induces anomalous anticyclonic circulation accompanied by subsidence, leading to significant positive temperature anomalies. Conversely, the anomalous cyclonic circulation near the Korean Peninsula, resulting from suppressed convection in the subtropical western Pacific, along with low‐level cold advection anomalies, contributes to a decrease in temperature. The spatial distribution of BSISO convection, which drives precipitation variation, shows a distinctive pattern of three meridionally narrow cells extending from the Philippines to the Korean Peninsula. Suppressed (enhanced) convection to the north of 20°N in the western North Pacific (WNP) promotes the northwestward expansion (eastward contraction) of the WNP Subtropical High in conjunction with a southwesterly (northeasterly) moisture flux anomaly. Furthermore, enhanced (reduced) moisture flux convergence and intensified ascending (descending) motion create favorable conditions for positive (negative) precipitation anomalies in South Korea. The combined effect of BSISOs not only amplifies the mean temperature and precipitation anomalies compared to individual modes but also increases the frequency of warmer, wetter, and drier events. Therefore, monitoring both BSISO modes together is crucial for comprehending and predicting the anomalous summer climate in South Korea.